Analysis of cadre knowledge with ability to score poedji rochjati score cards for pregnant women - Catur Wulandari; Rizki Amalia; Lailatul Khusnul Rizki (Universitas Nahdlatul Ulama Surabaya, 2022)
The ability of cadres to score Poedji Rochjati Score Cards for pregnant women will help midwives in early detection of the health of mothers and babies. The purpose of this study was to determine the relationship between knowledge of cadres and the ability to score Poedji Rochjati Score Cards in pregnant women. This study uses an analytical survey design with a cross sectional approach. A sample of 33 cadres was obtained using a simple random sampling technique from 35 populations. Data analysis used Spearman rank statistical test with 0.05. The results showed that there was a relationship between the knowledge of cadres and the scoring ability of the Poedji Rochjati Score Card, with a p value of 0.000 (< 0.05). Lack of knowledge of cadres related to the inability of cadres to score the Poedji Rochjati Score Card for pregnant women. Increased knowledge of cadres is needed so that cadres are able to score Poedji Rochjati Score Cards for pregnant women so that early detection can be done correctly.